2020
DOI: 10.1177/1177180120967958
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Indigenous peoples in Chile: vulnerability to contagion and mortality

Abstract: This research investigates whether Indigenous Populations are disproportionately vulnerable to COVID-19 infection and deaths in Chile. To answer this question, we use a regression model to analyze data from the Chilean government. Our analysis indicates that municipalities with a higher proportion of Indigenous people evinced higher rates of infection and deaths to COVID-19. Indigenous groups were not only highly affected at the beginning of the coronavirus outbreak; their rate of infection and mortality has i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 13 publications
1
9
0
1
Order By: Relevance
“…However, it has been found that this health situation has not affected all population sectors in Chile equally [ 10 ]. Thus, as for the indigenous population, the vulnerability indicators previously detected have increased since it is a group that already had inequalities in health [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been found that this health situation has not affected all population sectors in Chile equally [ 10 ]. Thus, as for the indigenous population, the vulnerability indicators previously detected have increased since it is a group that already had inequalities in health [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Chile this may be because the pluricultural of its population is not recognized, maintaining the idea of a homogeneous population, causing situations of racism and segregation, which recent efforts by the community are trying to reverse (Postero et al 2018). However, Chilean municipalities with larger indigenous populations exhibited high rates of infection and mortality, and this has not been mentioned by the government in its general reports (Millalen et al 2020).…”
Section: Linking Biodiversity With the Socio-economic And Health Cont...mentioning
confidence: 99%
“…Emerging evidence from Latin American countries suggests that the COVID-19 pandemic has disproportionately affected disadvantaged groups with low socioeconomic status as well as indigenous people, with large regional variation. [7][8][9][10] In Chile's capital, Santiago, areas with low socioeconomic status experienced poorer health interventions, and substantial excess mortality coupled with higher number of deaths and infection fatality rates at younger ages. 7 Similarly, municipalities with higher proportions of indigenous population is the author/funder, who has granted medRxiv a license to display the preprint in (which was not certified by peer review) preprint…”
Section: Introductionmentioning
confidence: 99%
“…The copyright holder for this this version posted December 9, 2021. ; https://doi.org/10.1101/2021.12.08.21267475 doi: medRxiv preprint showed higher mortality from COVID-19. 8 It is unclear, however, what the net effect of increased mortality has been on life expectancy at a more granular level of geography and by population subgroups in Chile.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation